Highly Selective Cyclooxygenase-1 Inhibitors P6 and Mofezolac Counteract Inflammatory State both In Vitro and In Vivo Models of Neuroinflammation - Calvello, Rosa; Lofrumento, Dario Domenico; Perrone, Maria Grazia; Cianciulli, Antonia; Salvatore, Rosaria; Vitale, Paola; De Nuccio, Francesco; Giannotti, Laura; Nicolardi, Giuseppe; Panaro, Maria Antonietta; Scilimati, Antonio (Frontiers in Neurology, 2017)
Activated microglia secret an array of pro-inflammatory factors, such as prostaglandins, whose accumulation contributes to neuronal damages. Prostaglandin endoperoxide synthases or cyclooxygenases (COX-1 and COX-2), which play a critical role in the inflammation, are the pharmacological targets of non-steroidal anti-inflammatory drugs, used to treat pain and inflammation. Since it was reported that COX-1 is the major player in mediating the brain inflammatory response, the aim of this study was to evaluate the effects of highly selective COX-1 inhibitors, P6 and mofezolac, in neuroinflammation models. Lipopolysaccharide (LPS)-activated mouse BV-2 microglial cells and LPS intracerebroventricular injected mice as in vitro and in vivo neuroinflammation models, respectively, were used to probe the antiinflammatory efficacy of P6 and mofezolac. Both P6 and mofezolac reduce COX-1 expression in LPS-activated BV-2 cells. This reduction was accompanied with PGE2 release reduction and NF-kB activation down-regulation. Coextensively, in the in vivo model, both GFAP and Iba-1 expression, two markers of inflammation, were reduced by mofezolac to a rank depending on the encephalon area analyzed. The increase of COX-1 expression observed in all the brain sections of LPS-treated mice was selectively down-regulated by the in vivo treatment with mofezolac as well as PGE2 release and IkBα phosphorylation amount assayed in the brain areas tested. These results indicate the capability of P6 and mofezolac to modulate the NF-kB signaling pathway, emphasizing the neuroprotective effect and therapeutic potential of COX-1 inhibitors in the control of neuroinflammatory diseases.